2018
DOI: 10.3389/fped.2018.00197
|View full text |Cite
|
Sign up to set email alerts
|

The Prebiotic and Probiotic Properties of Human Milk: Implications for Infant Immune Development and Pediatric Asthma

Abstract: The incidence of pediatric asthma has increased substantially in recent decades, reaching a worldwide prevalence of 14%. This rapid increase may be attributed to the loss of “Old Friend” microbes from the human microbiota resulting in a less diverse and “dysbiotic” gut microbiota, which fails to optimally stimulate immune development during infancy. This hypothesis is supported by observations that the gut microbiota is different in infants who develop asthma later in life compared to those who remain healthy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
93
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 77 publications
(111 reference statements)
1
93
0
6
Order By: Relevance
“…Previous studies have shown that human breast milk is microbially diverse and has both probiotic and prebiotic effects. 68 Breast milk contains Lactobacillus rhamnosus, Lactobacillus gasseri, Lactococcus lactis, Leuconostoc mesenteroides, and Bifidobacteria. 69 Microbiota in breast milk promote immune tolerance, prevent infection, and play a role in the maintenance of the epithelial barrier through an immune-mediated influence on intestinal microbiota composition.…”
Section: The Microbiome and Inflammatory Bowel Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that human breast milk is microbially diverse and has both probiotic and prebiotic effects. 68 Breast milk contains Lactobacillus rhamnosus, Lactobacillus gasseri, Lactococcus lactis, Leuconostoc mesenteroides, and Bifidobacteria. 69 Microbiota in breast milk promote immune tolerance, prevent infection, and play a role in the maintenance of the epithelial barrier through an immune-mediated influence on intestinal microbiota composition.…”
Section: The Microbiome and Inflammatory Bowel Diseasementioning
confidence: 99%
“…69,70 The oligosaccharides in breast milk have prebiotic effects that contribute to the establishment of the infant gut microbiota. 68 In addition, human milk oligosaccharides have been found to inhibit the adhesion of enteropathogenic E coli, Vibrio cholerae, and Salmonella fyris to epithelial cells. 71 Infants who are breast-fed have a lower incidence of gastrointestinal tract infections.…”
Section: The Microbiome and Inflammatory Bowel Diseasementioning
confidence: 99%
“…Microbes can impact on our lives in so many ways and are thus relevant to many personal decisions we take, such as whether to give birth by caesarean (aseptic) or natural delivery (colonization of the newborn by maternal microbes; Wampach et al, 2018), breast-feed [delivery to the baby of protective antibodies against pathogens, human milk oligosaccharides favouring bifidobacteria thought to orchestrate healthy development of immune systems (Gomez de Agüero et al, 2016;Moossavi et al, 2018), maternal microbes present in breast milk, etc. (Milani et al, 2017)], frequently use powerful disinfectants to clean the home (reduce exposure of infants to microbiome diversification and its health benefits: Finlay and Arrieta, 2016;Gilbert and Yee, 2016;Bach, 2018;Sharma and Gilbert, 2018; or indeed hospitals: see Caselli, 2017), be vaccinated or treated for an infection (Lane et al, 2018), use phosphorus-containing household cleaning products (Richards et al, 2015; can contribute to eutrophication and harmful algal blooms in local waters), use germicidal soaps (can cause dysbiosis of skin microbiota; Gilbert and Yee, 2016), acquire a companion dog (facilitates microbiota exchanges, Trinh et al, 2018; increases phosphorus inputs into the watershed, Hobbie et al, 2017) or what food to eat (e.g., beef, which has a substantial methane footprint; beef and dairy products whose consumption is correlated with cancers, zur Hausen et al, 2017; other meats and vegetables: provenance, shelf-life, associations with known risk factors, etc.)…”
Section: Microbes Pervasively and Profoundly Affect Us Personally Andmentioning
confidence: 99%
“…There is increasing appreciation for the impact of earlylife diet on "programming" of physiological systems with potential metabolic consequences in childhood or adulthood. More important, there is growing consensus that nutritional "programming effects" persist and influence risk for allergies, asthma, obesity, diabetes, and cardiovascular disease later in life [1,[19][20][21][22][23][24]. We hypothesized that neonatal diet (HM and MF) would differentially affect mitochondrial respiration in the small intestine (ileum) and liver.…”
Section: Introductionmentioning
confidence: 99%